HUBUNGAN SELF EFFICACY DENGAN SELF MANAGEMENT PASIEN DIABETES MELITUS DI PUSKESMAS HARAPANRAYA PEKANBARU - Tahuddin Badullah Saragih; Gamya Tri Utami; Wan Nishfa Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
One of the effort to prevent complications in diabetes mellitus patients is by improving the management of self management behavior for life, including self management related to health care. which influences and increases patients self management and patients self efficacy. The purpose this study is to determine the relationship between self efficacy and self management of patients with diabetes in the working area Puskesmas Harapan Pekanbaru. This research used descriptive correlation research design with a cross sectional approach. The research sample of 72 respondents were taken according to inclusion citeria by using purposive sampling technique. Measuring instruments in this study used a questionnaire. Analysis used is univariate analysis to determine the frequency distribution and bivariate analysis using Chi Square. The results of research on relationship of self efficacy and self management are of 39 respondents with high self efficacy 38 people (97,4%) with good self management and only I person with self management is sufficient. While the results for low self efficacy that have good self management there are only 22 people (66,7%) and with sufficient self management there are 11 people (33,3%). Based on the Chi Square result obtained p value = 0,000 < α (0,05) and it can be concluded that there is a relationship between self efficacy and self management in people with diabetes mellitus. Result of this study are recommended for people with diabetes mellitus to more attention to their health all components of self-management in a disclipned manner.Keywords: diabetes mellitus self efficacy, self management